FATIGUE IN MULTIPLE SCLEROSIS - Iryna Delva (Eastern Ukrainian Medical Journal, 2022)
The article discusses and analyzes literature data on the phenomenon of fatigue in patients with multiple sclerosis. More than 80% patients with multiple sclerosis complain of fatigue, which significantly limits their functional capacity and negatively affects the quality of life. In general, fatigue is a complex, multidimensional phenomenon that consists of subjective (one's own feeling of fatigue) and objective (quantitative characteristics of fatigue when performing a certain activity) components. At present, the most accessible method of fatigue assessment is patient survey. In multiple sclerosis, fatigue can be primary (as a direct consequence of the disease) or secondary (as a consequence of reduced functional capabilities, sleep disorders, chronic pain, side effects of medications, etc). In general, fatigue in multiple sclerosis is a heterogeneous phenomenon based on various etiopathogenetic mechanisms. We reviewed neuroimaging markers of global and focal lesions of the white and gray matter of the brain that are associated with the presence of fatigue in patients with multiple sclerosis. The impact of peripheral immune-inflammatory processes on the fatigue occurrence was shown which was realized via humoral, cellular, and neuronal mechanisms. We analyzed the role of inflammatory processes in the brain and spinal cord in the form of activation of microglia with hyperproduction of cytokines, which ultimately disrupts dopamine metabolism and reduces the affinity of dopamine receptors. The excess activity of certain functional components of the nervous system in the form of higher engagement of the motor structures of the brain and spinal cord during the performance of standard motor tasks was highlighted. The role of disruption of interoceptive mechanisms (perception and monitoring of the body's internal environment via hormonal, immune, metabolic, temperature, pain, and visceromotor signals) in the occurrence of fatigue in multiple sclerosis was shown. The paper underlines modern principles of fatigue correction based on these mechanisms.